Альтернативные технологии изготовления литейной оснастки - Таран, Борис Петрович; Пономаренко, Ольга Ивановна; Тринева, Т. Л. (Информационно-издательский дом "ЦентрИнформ", 2007)
Данная статья не только более подробно описывает технологические возможности применяемого при этом оборудования, но и посвящена рассказу об одном из самых эффективных и перспективных вариантов их реализации – изготовлению металлической оснастки методом Quick Cast, или так называемому "быстрому литью".

This article is a continuation of the topic about the technologies of rapid prototyping. The following material not only gives thorough description of technological capabilities of the used equipment but also deals with one of the most effective and promising variants of their production, namely, the production of metal rigging by the method Quick Cast. Thus, the present article covers such information: the capabilities of equipment and technologies Rapid Рrototyping, the experience of metal rigging production with the help of the technology Quick Cast.
Alternative Technologies of Casting Rigging Production
Keywords: трехмерное компьютерное проектирование; Центр новейших технологий; объемное сканирование; селективное лазерное спекание; оптико-цифровая установка; CAD-модель